Robotic Process Automation: a review of organizational grey literature - Chugh, Ritesh (2022)
Research on Robotic Process Automation (RPA) in the last decade has increased but lags behind developments in practice. This study explores the definition, evolution and categories of RPA, its benefits and challenges, identifies guidelines for implementation and provides a future outlook. Since there is an evident scarcity of comprehensive grey literature reviews in the area, this study presents an extensive narrative review of organizational grey literature on RPA by analyzing sixty-one organizational reports and white papers published between 2015 and 2020. This study provides a unified definition of RPA and groups the many categories of RPA into three types: basic automation, cognitive automation, and artificial intelligence. The study identifies the benefits of RPA and categorizes them into monetary; simplicity; efficiency and productivity; flexibility and scalability; reliability and consistency; compliance and governance; customer satisfaction; employee efficiency; and other long-term organizational benefits. The main challenges of RPA are awareness and perception of RPA; uncertainty about how to prepare for RPA; change management challenges while implementing RPA; and challenges associated with RPA vendors. Three main steps of RPA implementation are highlighted. This study provides practitioners and researchers with an extensive bird’s eye insight into RPA from an industry perspective.